Odpowiedzi

2010-03-26T14:43:08+01:00
A= (5¹⁶+25⁷):(26 × 5¹²)= (5^16+5^14):(26x5^12)=5^14(5^2+1):(26:5^12)=(5^14*26):(26*5^12)=5^2=25
B= (4√2 -2√3)(4√2 + 2√3)=16*2 -4*3=32-12=20 - ze wzoru skróconego mnożenia
a^-1=1/25
b^-1=1/20 czyli
b^-1>a^-1
^ potęga
1 5 1
2010-03-26T14:43:28+01:00
A = (5¹⁶+25⁷):(26 × 5¹²) = (5¹⁶+5¹⁴):(26×5¹²) = (5¹⁴×(5²+1)):(26×5¹²) = (26×5¹⁴):(26×5¹²)= 5² = 25
B = (4√2)² - (2√3)² = 32 - 12 = 20 (ze wzoru: "a² - b² = (a-b)(a+b)")

a⁻¹ = 25⁻¹ = 1/25 = 0.04

b⁻¹ = 20⁻¹ = 1/20 = 0.05

b⁻¹ > a⁻¹
2010-03-26T14:48:31+01:00
A=[5¹⁶+(5²)⁷]:(26 x 5¹²)=(5¹⁶+5¹⁴):(26 x 5¹²)=5¹⁴(5²+1):(26 x 5¹²)=(26x5¹⁴):(26x5¹²)=1x5²=25
B=(4√2)²-(2√3)²=32-12=20(wzór skróconego mnożenia)

A⁻¹=25⁻¹=0,04
B⁻¹=20⁻¹=0,05
A⁻¹<B⁻¹